Thermal entanglement and efficiency of the quantum Otto cycle for the su(1,1) Tavis-Cummings system - Chotorlishvili, Levan; Toklikishvili, Zaza; Berakdar, Jamal (Journal of physics. A, Mathematical and theoretical, 2011)
The influence of the dynamical Stark shift on the thermal entanglement and the efficiency of the quantum Otto cycle is studied for the su(1,1) Tavis-Cummings system. It is shown that the degree of the thermal entanglement becomes larger as the dynamical Stark shift increases. In contrast, the efficiency of the Otto cycle is degraded with an increase of the values of the dynamical Stark shift. Expressions for the efficiency coefficient are derived. Using those expressions, we identify the maximal efficiency of the quantum Otto cycle from the experimentally measured values of the dynamical Stark shift.